2006
DOI: 10.1002/art.22129
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic and metabolic biomarkers in the folate pathway and their association with methotrexate effects during dosage escalation in rheumatoid arthritis

Abstract: Objective. To evaluate the contribution of metabolites (methotrexate [MTX] and folate polyglutamate[PG] levels) and pharmacogenetic biomarkers in the folate pathway to the effects of MTX in patients with rheumatoid arthritis not previously treated with this antifolate.Methods. Forty-eight MTX-naive adult patients were enrolled in a prospective longitudinal study. MTX therapy was initiated at 7.5 mg/week and was increased every 4-6 weeks until a therapeutic response was achieved. Response was assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 34 publications
12
123
1
9
Order By: Relevance
“…In the present study, 93.75% of the patients with relapse were carriers of the T allele (Table III); this agrees with previous experimental studies, which identified the T allele as a risk for relapse to ALL (28). This suggests that the presence of the -A317G and C829T polymorphisms, and the strong association with the risk of relapse (p<0.05) (Table IV) may be a factor that led to more than 50% of deaths in the patients with ALL included in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 93.75% of the patients with relapse were carriers of the T allele (Table III); this agrees with previous experimental studies, which identified the T allele as a risk for relapse to ALL (28). This suggests that the presence of the -A317G and C829T polymorphisms, and the strong association with the risk of relapse (p<0.05) (Table IV) may be a factor that led to more than 50% of deaths in the patients with ALL included in this study.…”
Section: Discussionsupporting
confidence: 93%
“…To address this question, we determined the frequency of Tregs and CD39 + Tregs, as well as the density of CD39 expression on Tregs in RA patients before and after MTX treatment (at least 3 mo of MTX administration at doses ≥15 mg/wk). First, we demonstrated that the MTX resistance is not a consequence of a low availability of intracellular active MTX (22,23). We measured total MTX polyglutamate metabolites levels in erythrocytes from RA patients treated at least 3 mo with MTX.…”
Section: Resultsmentioning
confidence: 98%
“…It must be realized that other studies have shown an association between SHMT 1420CϾT, MTHFR 677CϾT, and MTHFR 1298AϾC with MTX efficacy (19,22). Due to our multiple stepwise backward statistical approach, only those factors contributing most to MTX efficacy at 6 months of treatment were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the influences of demographic, clinical, immunologic, and genetic factors on the state of disease in patients with RA have been studied (10)(11)(12)(13)(14)(15)(16)(17)(18). Specifically, polymorphisms in genes coding for methylenetetrahydrofolate reductase (MTHFR), adenosine monophosphate deaminase (AMPD1), aminoimidazole carboxamide ribonucleotide transformylase (ATIC), serine hydroxymethyltransferase 1 (SHMT1), and inosine triphosphate pyrophosphatase (ITPA) demonstrate association with the MTX response (19)(20)(21)(22). Nongenetic factors such as low disease activity at baseline, male sex, treatment with nonsteroidal antiinflammatory drugs (NSAIDs), and lower levels of creatinine clearance are also related to the efficacy of MTX (23).…”
mentioning
confidence: 99%